Singlet Oxygen Induced Products of Linoleates, 10- and 12-(Z,E)-Hydroxyoctadecadienoic Acids (HODE), Can Be Potential Biomarkers for Early Detection of Type 2 Diabetes - Umeno, Aya; Shichiri, Mototada; Ishida, Noriko; Hashimoto, Yoshiko; Abe, Kaori; Kataoka, Masatoshi; Yoshino, Kohzoh; Hagihara, Yoshihisa; Aki, Nanako; Funaki, Makoto; Asada, Yasuhiko; Yoshida, Yasukazu (PLOS ONE, 2013)
Current diagnostic tests such as glycemic indicators have limitations for early detection of impaired glucose tolerance (IGT), which leads to diabetes. Oxidative stress induced by various oxidants in a random and destructive manner is considered to play an important role in the pathophysiology of a number of human disorders and diseases such as impaired glucose tolerance. We have developed an improved method for the measurement of in vivo lipid peroxidation, where the presence of 8-iso-prostaglandin F2α (8-iso-PGF2α), hydroxyoctadecadienoic acids (HODEs), hydroxyeicosatetraenoic acids (HETEs), and 7-hydroxycholesterol (7-OHCh), as well as their parent molecules, linoleic acid (LA) and cholesterol (Ch), was determined by performing LC-MS/MS (for 8-iso-PGF2α, HODE, and HETE) and GC-MS (for 7-OHCh, LA, and Ch) after reduction with triphenyl phosphine and saponification by potassium hydroxide. We then applied this method to volunteers (n = 57), including normal type (n = 43), “high-normal” (fasting plasma glucose, 100–109 mg/dL, n = 7), pre-diabetic type (IGT, n = 5), and diabetic type (n = 2) subjects who are diagnosed by performing oral glucose tolerance tests (OGTTs). Several biomarkers in plasma, such as insulin, leptin, adiponectin, interleukin-6, tumor necrosis factor-α, high sensitivity-C-reactive protein, HbA1c, and glucose levels were measured during OGTT. We found that the fasting levels of (10- and 12-(Z,E)- HODE)/LA increased significantly with increasing levels of HbA1c and glucose during OGTT and with insulin secretion and resistance index. In conclusion, 10- and 12-(Z,E)-HODE may be prominent biomarkers for the early detection of IGT and “high-normal” type without OGTT.